Early Shi`i Thought: The Teachings of Imam Muhammad al-Baqir by Arzina R. Lalani (London: UK: I.B. Tauris in association with the Institute of Ismaili Studies, 2004. 192 pages.) (American Journal of Islam and Society, 2006)
The work under consideration is a clear and concise exposition of the lifeand thought of Muhammad al-Baqir, the great-grandson of ProphetMuhammad and one of the most influential Shi`i Imams, recognized by boththe Isma`ili and Ithna`ashari Shi`ahs. In this revised version of her doctoraldissertation, the author draws on a wide-range of primary sources and aselection of secondary materials in order to provide the reader with a portraitof a central figure in Shi`i Islam, one who can also tell us a great deal aboutthe formative stage of Islamic thought. For this reason, Early Shi`i Thoughtshould be of interest not only to students of Shi`ism, but also to all those concernedwith the often complex development of Islamic civilization during itsearly period.The first chapter, which serves as the introduction, constitutes a briefsummary of the lives of the first Shi`i Imams and the succession to theProphet. Here, the author provides us with a list of the primary sources thatshe will be using throughout her study. The second chapter, dealing with theimamate before the time of Muhammad al-Baqir, is also an historicaloverview of the lives of the early Imams and their struggles against both theUmayyads as well as some of their own partisans. Chapter 3 is devoted toal-Baqir’s succession to the imamate and to the divisions among the Shi`ahat that time. Al-Baqir’s quietism is contrasted with the political activism ofhis half-brother Zayd ibn `Ali and the emerging Zaydi Shi`ah, who werewilling to revolt against their rulers ...